Mpox across countries from Central and Eastern Europe - 2022 outbreak - Ianache, Irina; Skrzat-Klapaczynska, Agata; Jilich, David; Fleischhans, Lukas; Gmizic, Ivana; Ranin, Jovan; Papadopoulos, Antonios; Protopapas, Konstantinos; Mulabdic, Velida; Lakatos, Botond; Nagy, Eva Livia; Begovac, Josip; et al. (Travel medicine and infectious disease, 2024)
BACKGROUND: The aim of the study was to assess socio-demographical characteristics, clinical presentation, and outcomes in patients diagnosed with mpox. METHODS: A survey on patients diagnosed with mpox was performed in 14 countries from Central and Eastern Europe. Data was compared according to HIV status and country of origin (EU vs. non-EU). Mpox diagnosis was confirmed by RT-PCR from oropharyngeal swabs, skin lesions, and other body fluids. RESULTS: Out of 154 patients confirmed with mpox in 2022, 99.3% were males, with a median age (years) of 35 (IQR 30-39), 90.2% MSM and 48.7% PLWH. Compared to HIV-negative subjects, PLWH had more frequent high-risk behaviours:chemsex (p = 0.015), group sex (p = 0.027), and a history of sexually transmitted infections (STIs) (p = 0.004). Persons from EU were more often PLWH (p = 0.042), MSM (p < 0.0001), had multiple sexual partners (p = 0.025), practiced chemsex (p = 0.008) or group-sex (p = 0.005) and had more often history of STIs (p < 0.0001). The median CD4 cell count/mL at mpox diagnosis was 713 (IQR 486-996) and 73.5% had undetectable HIV VL. The commonest clinical features were fever (108 cases), lymphadenopathy (78), and vesiculo-pustular rash: penile (76), perianal (48), limbs (67). Fifty-one (31%) persons were hospitalized due to complications or epidemiological reasons. Three patients received tecovirimat or cidofovir. The outcome was favorable for all patients, including 4 with severe forms. CONCLUSIONS: Mpox was diagnosed predominantly in young MSM, with high-risk behaviors and history of STIs. Effective contact tracing and vaccination are important strategic pillars to control mpox outbreaks.
Keywords: epidemický výskyt choroby; Evropa; Sexually Transmitted Diseases; lidé středního věku; lidé; ženské pohlaví; Condylomata Acuminata; HIV Infections; Female; mužské pohlaví; HIV infekce; Europe; sexuálně přenosné nemoci; Adult; Europe, Eastern; Middle Aged; kondylomata akuminata; Humans; Disease Outbreaks; dospělí; Male; východní Evropa